A Study on the Effects of Chen-style and Yang-style Tai Chi Interventions on the Attention Characteristics of College Students - Li, Hong; Han, Qing; Gu, Huimin; Li, Cuihan; Zhang, Jianwei; Lyu, Shaojun (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: Research Objective: The Healthy China strategy reflects the upgraded health demands of the people, emphasizing not only physical health but also mental health and social adaptability. Contemporary college students are immersed in the order of the attention economy, characterized by strong curiosity and a strong desire for knowledge. The effective control of attention is an effective method for college students to improve learning efficiency, relieve stress, and improve mood. The fitness and health preservation ideas of Tai Chi, such as "yin-yang complementarity" and "calm mind and relaxed body", provide a valuable reference for solving current social problems related to human physical and mental health. There are numerous Tai Chi schools with distinct styles. Chen-style Tai Chi emphasizes spiral winding and alternating fast and slow movements during practice, while Yang-style Tai Chi requires gentle, smooth, and even movements. By exploring the impact and differences of different styles of Chen-style and Yang-style Tai Chi on the attention characteristics of college students, this study aims to provide feasible training methods for the regulation of attention characteristics. The significance of this research is to first provide empirical evidence for the impact of Tai Chi on physical and mental health; second, to help practitioners understand the principles of Tai Chi and provide guidance for Tai Chi teaching practice; and finally, to provide feasible training methods for attention characteristic improvement. Research Method: This study employs the methods of literature review, questionnaire survey, experiment, and mathematical statistics. Sample size calculation: G·power calculated a sample size of 51 people, with 17 people in each of the three groups. According to the recruitment requirements for subjects, 51 subjects were recruited from Hunan University of Humanities, Science and Technology. The inclusion criteria for subjects are: 1. Age between 18 and 30 years old; 2. Beginners interested in Tai Chi with less than one month of practice; 3. Good health without metabolic diseases; 4. Signed the informed consent form. The exclusion criteria are: 1. People with motor function disorders; 2. Those who have regularly practiced Tai Chi for a long time. Subjects signed the informed consent form, basic information was collected, and pre-tests were conducted. Random envelopes were generated by a third party and subjects were randomly assigned to three groups. Experimental intervention content was then carried out respectively. The intervention period was 12 weeks, with a frequency of 3 times per week and a duration of 1 hour. The movements were selected based on the competition routines of Chen-style and Yang-style Tai Chi, including basic movements such as forward step, backward step, parallel step, and fixed posture, as well as starting posture, Wild Horse Parts Mane, Reverse Rolling Up the Sleeve, Cloud Hands, and Single Whip. Post-tests were conducted after 12 weeks. The Attention Characteristics Scale was used to measure and evaluate the attention characteristics (attention transfer, attention span, attention stability, and attention distribution); the Stroop color-word test was also used to evaluate attention, and the test data were analyzed and sorted. Research Results: 1. After 12 weeks of experimental intervention, in the comparison of attention characteristics among the Chen-style Tai Chi group, Yang-style Tai Chi group, and the control group, there were significant main effects in the four dimensions of attention distribution (F(2,51) = 5.002, P = 0.011), attention span (F(2,51) = 4.562, P = 0.015), attention stability (F(2,51) = 7.66, P = 0.001), and attention transfer (F(2,51) = 4.554, P = 0.015). The P value was less than 0.01 for all four dimensions. 2. When comparing the data of the Chen-style Tai Chi group and the Yang-style Tai Chi group, there was a significant difference in attention distribution (P = 0.026), with the Yang-style group having better attention distribution than the Chen-style group; there was no significant difference in attention span (P = 0.870); there was a significant difference in attention stability (P = 0.045), with the Yang-style group having better attention stability than the Chen-style group; there was no significant difference in attention transfer (P = 0.254). In summary, there was no difference in attention span and attention transfer between the Chen-style and Yang-style groups, but the Yang-style group had better attention distribution and attention stability than the Chen-style group. After 12 weeks of experimental intervention, the Stroop color-word test results of the three groups showed that there was no significant main effect in RT and ACC (RT (P = 0.501), ACC (P = 0.667)). However, there was a significant difference in RT (P = 0.03) within the Chen-style group and Yang-style group before and after the intervention, while there was no significant difference in ACC (0.252). Research conclusion: 1. After 12 weeks of experimental intervention, the attention characteristics of the Chen-style Tai Chi group and Yang-style Tai Chi group were better than those of the control group. Therefore, Chen-style Tai Chi and Yang-style Tai Chi can improve the attention characteristics of college students. 2. There are differences in attention characteristics between Chen-style Tai Chi and Yang-style Tai Chi. Yang-style Tai Chi is superior to Chen-style Tai Chi in attention allocation and attention stability, while there is no significant difference in attention span and attention transfer. Only a trend of Chen-style Tai Chi being better is shown. 3. The practice of Chen-style Tai Chi and Yang-style Tai Chi can awaken and obtain internal attention awareness. Based on the research conclusion, the hypothesis of this study is verified. This study suggests that in Tai Chi practice, one should persist in practicing for a long time, as the stimulating effect on attention characteristics will be better. For beginners, it is recommended to choose Yang-style Tai Chi for practice first, as it is easier to learn. Chen-style Tai Chi is more difficult to practice and less likely to show results. After achieving a relatively stable level in Yang-style Tai Chi practice, Chen-style Tai Chi can be added to further improve other dimensions of attention characteristics.